Perception of American–English Vowels by Early and Late Spanish–English Bilinguals. (December 2019) - Baigorri, Miriam; Campanelli, Luca; Levy, Erika S.
Increasing numbers of Hispanic immigrants are entering the US and learning American–English (AE) as a second language (L2). Previous studies investigating the relationship between AE and Spanish vowels have revealed an advantage for early L2 learners for their accuracy of L2 vowel perception. Replicating and extending such previous research, this study examined the patterns with which early and late Spanish–English bilingual adults assimilated naturally-produced AE vowels to their native vowel inventory and the accuracy with which they discriminated the vowels. Twelve early Spanish–English bilingual, 12 late Spanish–English bilingual, and 10 monolingual listeners performed perceptual-assimilation and categorical-discrimination tasks involving AE /i, ɪ, ɛ, ʌ, æ, ɑ, o/. Early bilinguals demonstrated similar assimilation patterns to late bilinguals. Late bilinguals' discrimination was less accurate than early bilinguals' and AE monolinguals'. Certain contrasts, such as /æ-ɑ/, /ʌ-ɑ/, and /ʌ-æ/, were particularly difficult to discriminate for both bilingual groups. Consistent with previous research, findings suggest that early L2 learning heightens Spanish–English bilinguals' ability to perceive cross-language phonetic differences. However, even early bilinguals' native-vowel system continues to influence their L2 perception.